Evaluation of pharmacists' knowledge of women's issues in epilepsy: A cross-sectional study in Palestinian pharmacy practice. (March 2017) - Shawahna, Ramzi; Atrash, Ahlam; Jebril, Aman; Khalaf, Areen; Shaheen, Eman; Tahboosh, Hala
Graphical abstract: Highlights: Pharmacists can provide vital information to women with epilepsy. Knowledge is related to interacting with ≥10 patients with epilepsy. Greater exposure to people with epilepsy might improve pharmacist's knowledge. Abstract: Purpose: Pharmacists are key players in providing healthcare for patients with chronic diseases including women with epilepsy. The purpose of this study was to assess pharmacist's knowledge of women's issues in epilepsy in the Palestinian pharmacy practice. Method: The study was conducted in a cross-sectional observational design using a 12-item test on women's health in epilepsy. Demographic details were collected. Scores were calculated as percentage of correct answers for each pharmacist. Results: The sample consisted of 408 pharmacists. The median correct score was only 53.8% with an IQR of 30.8. Pharmacists who interacted with ≥10 patients with epilepsy per month were 1.61 (95% C.I of 1.04–2.49) more likely to score ≥60% in the test than those who interacted with <10 patients with epilepsy per month. The difficulty index ranged from very easy to difficult. Nearly 91% of the pharmacists answered correctly the question on the role of folic acid in reducing teratogenesis and only 46% answered correctly the question on exposure to valproic acid and the risk of giving birth to a child with autism. Conclusion: Although pharmacists could be knowledgeable and in key position to provide essential information to patients with chronic diseases, there are many knowledge gaps in women's health issues in epilepsy that need bridging. Greater exposure to and interaction with people with epilepsy might be helpful in enhancing knowledge of pharmacists of specific issues pertaining to women's health in epilepsy.